2012
DOI: 10.1186/1478-4491-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Human resources for health care delivery in Tanzania: a multifaceted problem

Abstract: BackgroundRecent years have seen an unprecedented increase in funds for procurement of health commodities in developing countries. A major challenge now is the efficient delivery of commodities and services to improve population health. With this in mind, we documented staffing levels and productivity in peripheral health facilities in southern Tanzania.MethodA health facility survey was conducted to collect data on staff employed, their main tasks, availability on the day of the survey, reasons for absenteeis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
137
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 40 publications
13
137
1
Order By: Relevance
“…In Tanzania, oral health screening services in primary health settings, particularly in reproductive and child health is inadequately addressed partly because the health care providers in these settings have little knowledge [14,15] and is partly due to the shortage of the oral health workforce. [16][17][18] In South Africa, like in Tanzania, there is minimal integration of oral health education at reproductive and child health sites. [19] According to this finding in South Africa; reproductive and child health sites remain important sites for integration of dental and oral health care with general health services.…”
Section: Early Childhood Caries (Ecc) In Tanzania and Other Eastmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, oral health screening services in primary health settings, particularly in reproductive and child health is inadequately addressed partly because the health care providers in these settings have little knowledge [14,15] and is partly due to the shortage of the oral health workforce. [16][17][18] In South Africa, like in Tanzania, there is minimal integration of oral health education at reproductive and child health sites. [19] According to this finding in South Africa; reproductive and child health sites remain important sites for integration of dental and oral health care with general health services.…”
Section: Early Childhood Caries (Ecc) In Tanzania and Other Eastmentioning
confidence: 99%
“…A study conducted in a recent year revealed that only 14% of the recommended number of nurses and 20% of the clinical staff had been employed at the health facilities. [18] Human resources for health constraints are more severe in oral health arenas. According to the ministry of health, community development, gender, elderly and children (MoHCDGEC) report of 2012/2013, Tanzania had dentist-to-population ratio of 1:120,000 which is very low compared to that recommended by the World Health Organization of 1:7,500.…”
Section: Dental Care In Tanzaniamentioning
confidence: 99%
“…Absenteeism is a major problem; key staff members may spend most of their time attending trainings or report ill frequently [17] resulting in low health worker performance and outputs. Inadequate staffing levels may be compounded by a high level of absenteeism which reduces access to services [18]. It has been noted that a fair and accurate performance review may begin with tracking employee behaviours and patterns [19] for example introducing registers of arrival and departure time.…”
Section: Introductionmentioning
confidence: 99%
“…This represents a form of wastage, especially if shortages of those skills exist in the country [17]. Health workers' job descriptions are often unavailable [18] and workloads do not match staffing levels [17]. A substantial portion of staff time may be spent on administrative duties [17] as opposed to treatment and caring activities [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation